Social support and the serotonin transporter genotype (5‐HTTLPR) moderate levels of resilience, sense of coherence, and depression. Issue 5 (18th May 2015) - Reinelt, Eva; Barnow, Sven; Stopsack, Malte; Aldinger, Maren; Schmidt, Carsten Oliver; John, Ulrich; Grabe, Hans Jörgen
Abstract : Gene x environment interactions have mainly been investigated in models of psychopathology. However, the putative interplay between genes and beneficial environmental conditions on positive outcomes has rarely been addressed. We therefore examined the interaction between the serotonin transporter linked polymorphic region (5‐HTTLPR) and social support on the sense of coherence (SOC), resilience, and depressive symptoms. Furthermore, we scrutinized our examinations by differentiating between individuals with and without childhood abuse. The sample included 1, 811 participants from the general population (Study of Health in Pomerania, Germany). The triallelic genotype of 5‐HTTLPR was determined and longitudinal data of social support were used. Among individuals with high social support no significant differences between 5‐HTTLPR genotypes regarding all outcome variables were found. However, among those with low social support, carriers of at least one short allele reported significantly increased levels of SOC and resilience, as well as less depressive symptoms than carriers of the l/l genotype. This result was not modified by differentiating between those with childhood abuse and those without. In less supportive social environments the impact of distinct genotypes on behavioral outcomes might be more relevant than in supportive environments where social compensation might take place. Our findings indicate that both alleles of 5‐HTTLPR contribute to the adaptability to different environmental conditions. © 2015 Wiley Periodicals, Inc.